Anodized aluminum-silicon alloy counter electrode substrates for next generation solar cell applications - ALPAY SARI, NESLİHAN (ELSEVIER SCIENCE BV, 2015)
Aluminum-silicon (Al-Si) alloy based counter electrode substrates were developed for next generation solar cells. Controlled anodization was performed on the Al-Si alloys to form an aluminum oxide (AO) with corrosion resistant microstructure. Presence of secondary Si particles in the Al-Si alloy system facilitated electrical conduction across the insulating AO film. In this way, aluminum is rendered suitable as substrate for photovoltaic applications without having to resort to its coating with costly conductive metals such as titanium. Current density-voltage (J-V) measurements of dye-sensitized solar cells (DSSCs) based on the new Al-Si alloys yielded a high power conversion efficiency (eta) of up to 6.13% under 1 Sun illumination condition, essentially matching the conversion efficiency, eta = 6.7%, of a reference DSSC with fluorine-doped tin oxide (FTO) glass based electrode substrates. The microstructure of the Al-Si alloys and the anodized oxide films was studied in detail by FE-SEM and XPS and correlated to the device performance. Differences between the photovoltaic characteristics of the cells were analyzed further by electrochemical impedance spectroscopy and optical reflectance spectroscopy measurements. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Aluminum; Counter electrode; Anodization; Photovoltaic device; Dye-sensitized solar cell; TIO2 FILMS; METAL-SUBSTRATE; LOW-COST; PERFORMANCE; FABRICATION; EFFICIENCY; SHEET; SPECTROSCOPY; SENSITIZER; PROGRESS